Epistemic Injustice and Performing Know-how. (2nd November 2021) - Barker, Beth
ABSTRACT: In this paper, I expand our framework for epistemic injustice by shifting focus from epistemic evaluations of individuals in information exchange to epistemic evaluations of individuals engaging their know-how in performance. I call the injustice to individuals qua knowers-how performative injustice, and I argue that performative injustice has distinct features worth understanding apart from varieties of epistemic injustice devoted to information exchange. I develop an account of the performative authority that is unfairly evaluated in cases of performative injustice and show how, in some cases, cognitive penetration can affect observers' evaluations. Finally, I show how stereotype threat may short circuit what would otherwise be cases of performative injustice, which in turn reveals the significance of its systemic manifestations.